Internet usage elevates elderly obesity: evidence from a difference-in-differences analysis of the broadband China policy - Lin Guo; Jia Song; Li Yang; Ziyi Wu; Hengzhi Shi; Lixiang Song; Tianmiao Dong; Linlin Yue; Yunwei Li; Ying Liu (Archives of Public Health)
Abstract Background The global aging population is rapidly increasing, which has led to a growing prevalence of obesity among the elderly. Body mass index (BMI) is a crucial measure of obesity and is linked to an increased risk of various chronic diseases. At the same time, the widespread use of the internet and digital technologies has significantly influenced the health behaviors and outcomes of the elderly. Objective This study aims to examine the causal relationship between internet usage and BMI among the elderly, addressing a gap in existing research and providing evidence for the development of health policies targeted at the elderly population. Methods Utilizing China’s “Broadband China” strategy as a quasi-natural experiment, we employed a difference-in-differences (DID) approach to analyze panel data from the CHARLS covering the years 2011–2015. By comparing the treatment and control groups before and after the policy’s implementation, we identify causal effects. Results Our findings indicate that the “Broadband China” strategy significantly increased BMI among the elderly. The mechanisms underlying this effect include reduced sleep duration, decreased physical activity levels, and worsened mental health. Furthermore, the impact of internet usage on obesity is particularly pronounced among urban residents, those without chronic diseases, and individuals with fewer surviving children. Conclusions Policy recommendations include promoting healthy internet usage practices, enhancing community-based activity facilities, and providing comprehensive mental health support to mitigate obesity rates and improve health outcomes among the elderly.